Tinjauan Teologis tentang Tarian dan Manfaatnya bagi Pertumbuhan Rohani - Eunike Eunike (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2021)
Dance is strongly connected to life, freedom, salvation, restoration and victory over the enemies. The Bible uses the word dance for the first time in the verse when Miriam took her tambourine and led the Israelites in a victorious dance after they had been set free from the Egyptians, who chased them into the red sea. God gave them salvation, victory, deliverance, and life. Miriam’s dance was a respond and expression of victory over the enemies (Ex. 15:20). Dance or body movement is a language of communication equal to words, music, or other expressed art. For this reason, when a dance is communicating the word of God, for certain people or in certain situations then it could becalled a prophetic dance. To be a dancer is a great calling. A calling to bring back what has been taken from heaven, a calling to love God more and more, a calling to make a new covenant between men and God. Prophetic dance is a way to serve God through dance. In this way a dancer is not an artist who chooses to be served rather than to serve. But the principle is when one is appointed to be a leader, the more is his responsibility to serve his brethrens. Every movement is a body language to communicate the messages. Within the context of dance, every movement should carry a message in a way that people would understand the meaning when they see the dance.